Evaluating the Effectiveness of Identity Exploration Workshops on Self-Esteem and Emotional Maturity - Rodrigues da Silva, Diana; Okonkwo, Adaeze; Mwangi, Grace (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: This study aimed to evaluate the effectiveness of identity exploration workshops in enhancing self-esteem and emotional maturity among Nigerian adolescents and young adults. Methods and Materials: A randomized controlled trial design was employed with 30 participants aged 16 to 21, recruited from educational institutions in Nigeria. Participants were randomly assigned to either an experimental group (n = 15), which received a nine-session identity exploration workshop, or a control group (n = 15), which received no intervention. The workshop was delivered over nine weeks, with each session lasting 60 minutes and focusing on different aspects of identity, values, emotions, and interpersonal roles. Self-esteem was measured using the Rosenberg Self-Esteem Scale (RSES), and emotional maturity was assessed using the Emotional Maturity Scale (EMS) by Singh and Bhargava. Assessments were conducted at pre-test, post-test, and five-month follow-up. Data were analyzed using repeated measures ANOVA and Bonferroni post-hoc tests in SPSS-27. Findings: Participants in the experimental group showed a significant increase in self-esteem scores from pre-test (M = 22.87, SD = 3.45) to post-test (M = 29.13, SD = 3.78), and these gains were sustained at follow-up (M = 28.80, SD = 3.56). Emotional maturity scores significantly decreased from pre-test (M = 125.27, SD = 7.96) to post-test (M = 109.07, SD = 8.31), with sustained improvements at follow-up (M = 110.00, SD = 7.85), indicating enhanced emotional maturity. The control group exhibited no significant changes across time. ANOVA results revealed significant time × group interactions for both variables (p < .001), and Bonferroni post-hoc tests confirmed the stability of improvements over time. Conclusion: Identity exploration workshops are effective in promoting both self-esteem and emotional maturity among adolescents and young adults, with effects lasting beyond the intervention period. These findings support the integration of identity-based developmental programs in educational and youth support settings.